Research on sweat metabolomics of athlete’s fatigue induced by high intensity interval training - Meihua, Su; Jiahui, Jin; Yujia, Li; Shuang, Zhao; Jingjing, Zhan (Frontiers in Physiology, 2023)
Objective: Sweat is an important specimen of human metabolism, which can simply and noninvasively monitor the metabolic state of the body, and its metabolites can be used as biomarkers for disease diagnosis, while the changes of sweat metabolites before and after exercise-induced fatigue are still unclear. Methods: In this experiment, high-performance chemical isotope labeling liquid chromatography-mass spectrometry (LC-MS) was used to metabolomic 28 sweat samples before and after exercise-induced fatigue of 14 long-distance runners, also IsoMS PRO and SPSS22.0 software were used to analyze the metabolite changes and differential metabolic pathways. Results: A total of 446 metabolites with high confidence were identified, and the sweat metabolome group before and after high-intensity interval exercise-induced fatigue was obvious, among which the up-regulated differential metabolites mainly included hypoxanthine, pyruvate, several amino acids, etc., while the down-regulated differential metabolites mainly included amino acid derivatives, vitamin B6, theophylline, etc. Conclusion: The change of hypoxanthine concentration in sweat can be used as a good biomarker for the diagnosis of exercise-induced fatigue, while the change of pyruvate content in sweat can be used as a discriminant index for the energy metabolism mode of the body before and after exercise. The main metabolic pathways involved in differential metabolites produced before and after HIIT exercise-induced fatigue are purine metabolism and amino acid metabolism.